Hypergeometric τ Functions of the q-Painlevé Systems of Type (A₂+A₁)⁽¹⁾ - Nakazono, N. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
We consider a q-Painlevé III equation and a q-Painlevé II equation arising from a birational representation of the affine Weyl group of type (A₂+A₁)⁽¹⁾. We study their hypergeometric solutions on the level of τ functions.